Faces presenting sadness enhance self‐control abilities in gifted adolescents. (23rd February 2018) - Urben, Sébastien; Camos, Valérie; Habersaat, Stéphanie; Stéphan, Philippe
Abstract : Self‐regulation skills refer to processes allowing emotional and cognitive adaptation of the individual. Some gifted adolescents are known for their imbalance between high intellectual abilities and low emotional skills. Thus, this study aimed at examining the interplay between emotion and cognition in gifted and non‐gifted adolescents. A stop‐signal task, a response inhibition task including neutral, happy, or sad faces as signal triggering inhibition, was administered to 19 gifted and 20 typically developing male adolescents (12–18 years old). Gifted adolescents showed lower response inhibition abilities than non‐gifted adolescents in the neutral and happy face conditions. Sad faces in gifted adolescents were associated with higher response inhibition compared to happy condition. In typically developing adolescents, emotional information (happy or sad faces) was related to lower response inhibition compared to neutral face condition. This study highlights that gifted adolescents present different self‐regulation skills than their typically developing peers. Statement of contribution What is already known on this subject? Some gifted adolescents present higher intellectual abilities alongside with lower socio‐emotional skills. Self‐regulation skills refer to processes allowing emotional and cognitive adaptation. Self‐regulation skills might help to understand gifted adolescents, but remain scarcely studied. What does this study adds? Task‐relevant emotional information impaired cognitive control in typically developing adolescents. Gifted adolescents are able to use sad faces to enhance their cognitive control abilities.